KARAKTERISTIK PENDERITA KONJUNGTIVITIS BAKTERI TAHUN 2022-2024 DI RUMAH SAKIT UNIVERSITAS ANDALAS - Haves Ashan; Zabilla Az Zahra; Insil Pendri Hariyani; Seres Triola (Yayasan Nusantara Hasana Berdikari, 2026)
Bacterial conjunctivitis is conjunctivitis caused by bacteria. In developing countries, infectious conjunctivitis is often caused by bacterial conjunctivitis. Conjunctivitis can occur at any age, from children to adults, and can affect both genders. This study aimed to determine the characteristics of patients with bacterial conjunctivitis in 2022–2024 at Andalas University Hospital. The study was conducted in the field of ophthalmology from September to November 2025 using a descriptive quantitative method with secondary data. The accessible population consisted of all patients diagnosed with bacterial conjunctivitis at Andalas University Hospital, Padang. Sampling was performed using simple random sampling, involving 96 respondents. Data were analyzed using frequency distributions and processed using the computerized IBM SPSS version 26.0 program. The results showed that most respondents were in their late teens (17–25 years), comprising 18 people (18.8%), female, comprising 51 people (53.1%), and unemployed, comprising 54 people (56.3%). The most frequent clinical symptoms were unilateral hyperemia, observed in 84 patients (87.5%), serous discharge in 35 patients (36.5%), and lacrimation within the normal category in 55 patients (57.3%) at Andalas University Hospital, Padang, in 2023–2024. It was concluded that most patients with bacterial conjunctivitis were in their late teens (17–25 years), female, and unemployed. The most common clinical symptom was unilateral hyperemia, while the most frequent type of discharge was serous discharge, and lacrimation was generally within the normal range.